WristDial: An Eyes-Free Integer-Value Input Method by Quantizing the Wrist Rotation. Issue 17 (21st October 2021) - Youn, Eunhye; Lee, Sangyoon; Kim, Sunbum; Shim, Youngbo Aram; Chan, Liwei; Lee, Geehyuk
ABSTRACT: Smartwatches are a convenient substitute for smartphones in hand-busy situations, but there is limited interactivity to one-handed use of wrist-worn devices. In this paper, we propose WristDial, a one-handed integer input technique which uses quantization of the angular distance of the wrist rotation with nonvisual feedback. Using tactile feedback, we present four techniques based on counting of tactile stimuli. With one of them, 94.44% average accuracy and 2.81 s average completion time were acquired in the task of entering a number from the range 1 to 10. We also evaluate the quantitative performance of the combination of interruptible speech and non-speech auditory feedback. Our results show that when speech feedback exists, adding a continuous change of pitch or clicking sound at the boundaries does not have a significant effect on the performance. Using only speech feedback, 95.47% accuracy and 1.45 s completion time were acquired.